2015
DOI: 10.1016/j.genhosppsych.2015.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Review of the evidence: prevalence of medical conditions in the United States population with serious mental illness

Abstract: Objective Persons with serious mental illness (SMI) have high rates of premature mortality from preventable medical conditions, but this group is underrepresented in epidemiologic surveys and we lack national estimates of the prevalence of conditions such as obesity and diabetes in this group. We performed a comprehensive review to synthesize estimates of the prevalence of 15 medical conditions among the population with SMI. Method We reviewed studies published in the peer-reviewed literature from January 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
82
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 153 publications
(88 citation statements)
references
References 99 publications
3
82
1
2
Order By: Relevance
“…The previous study mentioned that people with psychiatric disorders reported higher odds of multiple chronic medical conditions compared with people without psychiatric disorders . The prevalence of medical conditions among the population with severe mental illness was higher than that among the overall population . Lifestyle, psychotropic medication side effects, and poorer quality of health care received can account for much of the increased risk of physical diseases in mental disorders .…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…The previous study mentioned that people with psychiatric disorders reported higher odds of multiple chronic medical conditions compared with people without psychiatric disorders . The prevalence of medical conditions among the population with severe mental illness was higher than that among the overall population . Lifestyle, psychotropic medication side effects, and poorer quality of health care received can account for much of the increased risk of physical diseases in mental disorders .…”
Section: Introductionmentioning
confidence: 98%
“…The prevalence of medical conditions in a mental population estimated varied considerably due to different measurement and study populations . In past research, most mental disorders were identified using epidemiological self‐report during a structured or semistructured interview .…”
Section: Introductionmentioning
confidence: 99%
“…Individuals with SMI—defined as a mental illness like schizophrenia or bipolar disorder that results in substantial functional impairment—are particularly likely to experience significantly reduced life expectancy. A report by Parks et al raised national awareness by stating that people with SMI die decades earlier in our country compared with the general population . Most of this disparity is related to preventable and treatable chronic conditions, such as cardiovascular disease and cancer, with studies finding that, similar to the general population, cancer is the second leading cause of death .…”
Section: Introductionmentioning
confidence: 98%
“…Adults with serious mental illness (SMI) are more likely to suffer from chronic physical health conditions, such as diabetes, cardiovascular disease and hypertension, than the general population (Janssen, McGinty, Azrin, Juliano-Bult, & Daumit, 2015; Osborn et al, 2008). Those physical health conditions are the primary drivers of early mortality in this population; SMI is associated with about 8 years of reduced life expectancy (B.…”
Section: Introductionmentioning
confidence: 99%